Transformasi Pendidikan Inklusif: Model Inovatif 'Inclusionplus' untuk Meningkatkan Akses dan Dukungan bagi Anak-anak Berkebutuhan Khusus - Hasmira Said; Yaman La Ndibo; Roni Amaludin; Lilianti Lilianti; Nasir Nasir (Journal of Education and Teaching (JET), 2024)
This research aims to develop an inclusive education model " InklusiPlus" in Kendari City for children with special needs. The research's goal is to enhance access and support to create an inclusive educational environment. Through a collaborative approach, the study focuses on establishing a Collaborative Forum, professional training, developing inclusive facilities, and raising community awareness campaigns. The research involves 36 participants, including children with special needs, educators, and parents at Special Schools in Kendari City. Data collection is conducted through observations and interviews. Qualitative analysis is employed for data analysis. The results indicate that "InklusiPlus" successfully enhances collaboration among stakeholders, provides relevant training, and creates inclusive facilities. The research's conclusion highlights the success of the "InklusiPlus" model in creating an inclusive environment that supports the development of children with special needs in Kendari City.